Factors associated with health dissatisfaction of elementary school teachers - Ediálida Costa Santos; Mariano Martínez Espinosa; Samira Reschetti Marcon; Annelita Almeida Oliveira Reiners; Marília Duarte Valim; Bryan Mariano Martínez Alves
ABSTRACT Objective: To evaluate factors associated with health dissatisfaction of public elementary school teachers. Methods: Cross-sectional study conducted among teachers from a Midwest capital, in 2017. A self-administered questionnaire composed of a collection of validated instruments and additional questions was used. Poisson Regression was performed, considering significance p <0.05. Results: sample composed of 326 teachers, with an average age of 43 years, 87.1% female. Concerning health conditions, 19.5% were dissatisfied and 31.5% were indifferent. In a simultaneous analysis of the factors of interest, a statistically significant association was found among teacher's health dissatisfaction and the presence of symptoms of common mental disorders (PRa= 2.28), musculoskeletal symptoms in the last 12 months (PRa= 1.71), voice disorders (PRa= 1.29), never/rarely waking up rested (PRa= 1.45), never/rarely engage in physical activity/sports (PRa= 1.57), among other factors. Conclusion: never/rarely waking up rested and engaging in physical activity/sports, the presence of common mental disorders, musculoskeletal symptoms and voice disorders were associated with health dissatisfaction.